SENSITIVILITY PROFILE HEP-G2 AS A MODEL OF CYTOTOXIC ACTIVITY DETERMINATION OF BIOACTIVATED XENOBIOTICS VIA CYP 450 - Stephanie O. PRIETO; Fabio A. ARISTIZÁBAL G. (Vitae, 2009)
Several methodologies have been proposed in order to establish anticancer action, mainly focused on in vitro cytotoxicity valuation on neoplasic cell lines derived from human cancer. However, most of these cell lines are metabolically incompetent, restricting model sensibility and generating false negative answers. Hep-G2 cell line is widely used because of its high sensibility reflecting phase I and II activity of some enzymes of phase I and II, which play an important role in activation and detoxification of xenobiotics. In this study, Hep-G2 is used as a model to find cytotoxic activity produced by 2-amino- 1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) and Cyclophosphamide, in presence or absence of inductor agents. This analysis was carried out by measuring indirectly viable number of cells with assays like MTT and resazurine staining. In addition, the possibility of co-cultures with other cell lines was evaluated according to strengthen method sensibility. Cytotoxicity of PhIP and cyclophosphamide was observed with the cellular staining methods. For this reason a co-culture system was established. The answer was similar to independent cell lines. These results propose that pre-treated Hep-G2 cells with some inductive agents show sensibility by PhIP as different authors postulate.